TUMBUHAN INANG DAN DAYA MAKAN KEONG MAS (Pomacea canaliculata) PADA BEBERAPA VARIETAS PADI DI KABUPATEN MALAKA - Jacqualine Arriani Bunga; Nina Jeni Lapinangga; Jemrifs H. H. Sonbai (Partner, 2018)
This study is entitled "Host Plants and Eating Ability of Keong Mas (Pomaceacanaliculata) in some Paddy Varieties in Malaka District". Keong Mas are type of snails which are considered as invasive pests. In Malaka, in 2010-2012 there was a snail boom which caused severe damage to rice to “puso”. This study had been conducted from June 2018 to November 2018. The research aims to study the host plants and the ability to eat of the snails in several rice varieties. The snails were tested for its ability to feed on water plants which were considered as alternative hosts of paddyplants. Host testing was undertaken through forced testing and selective testing of several aquatic plants in rice fields. The eating ability test was carried out on four weeks old paddy varieties cultivated by farmers in Malaka. Fifty rice seedlings were planted in a circle, ten seedlings perplanting hole and were repeated for four times. The number of seeds which were encroached by the juvenile snails was tabulated and analyzed. The result shows that 6 succulent plants were favored by the snails, namely Limnocharis flava, Colocasia esculenta, Ludwigiaadscendens, Monochoriavaginalis, Ipomoea aquatica and Cat tile / Sasoser (Typha spp). The most vulnerable paddy seeds to snails are Ciherang (a), Mapan, Impari 12 (ab), Mokongga (bc), IR 68, Sibogo, and Red Rice (cd), and the most resistant to snails' is Black Rice variety (d).